Determination of clostebol residues in the urine of slaughter animals using liquid chromatography–tandem mass spectrometry - Matraszek-Żuchowska Iwona; Kłopot Alicja; Grzelak Justyna; Zdonek Paulina (Journal of Veterinary Research)
Synthetic anabolic hormones, which may pose a potential risk to human health, should not be used in fattening food-producing animals. Because of the hormonal effects they cause, growth-promoting compounds are banned by legislation in the EU for use in animal husbandry. Consequently, all EU member states are required to conduct monitoring tests on the content and residues of these compounds in prescribed biological matrices to ensure the safety of food consumers. The aim of this research was to develop a liquid chromatography–tandem mass spectrometry method for the detection of the residue of one such anabolic hormone, clostebol in food animal urine.